Pengaruh Model Pembelajaran RANGKA (Rumuskan, Amati, Nyatakan, Gabungkan, Komunikasikan dan Amalkan) Terhadap Keterampilan Berpikir Kritis Peserta Didik Materi Ajar Sel Kelas XI IPA 2 SMAN 1 Wonomulyo - Mursidin, Wahyudi; Marjuni, Marjuni; Zulkarnaim, Zulkarnaim (Al-AHYA: Jurnal Pendidikan Biologi, 2025)
This study was designed to investigate the impact of implementing the RANGKA learning model on students’ critical thinking skills. A quantitative approach was used with a quasi-experimental research design, applying a pretest-posttest design with a control group. The research population included all 11th grade science students at SMAN 1 Wonomulyo, while the sample selection was conducted using purposive sampling, where the 11th grade science class 2 was designated as the control group and 11th grade science class 3 as the experimental group. The data collection instrument was an essay test, and data analysis was conducted using descriptive and inferential statistics. The results showed that the average critical thinking score of students in the control group was 51.83, while the experimental group was 65.50. Inferential analysis produced a significance value of 0.000, which is lower than the threshold of α = 0.05, so the null hypothesis was rejected and the alternative hypothesis was accepted. These findings confirm that the RANGKA learning model has a significant effect on the development of critical thinking skills among 11th grade students at SMAN 1 Wonomulyo